Analisis Struktur Modal Terhadap Profitabilitas Pada Perusahaan Sub Sektor Semen Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2022 - Yuvita Arianti Doing; Andreas Rengga; Konstantinus Pati Sanga (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
This research animed to: (1) determine the description of Profitability aand Capital Structure, (2) analyze the effect of Capital Structure on Profitability either partially or simultaneously. The type of research used was quantitative research with an associative approach. The research population was the Cement Sub Sector companies listed on the Indonesia Stock Exchange. The sample used were the financial statements of Cement Sub Sector companies for the period 2013-2022, using a purposive sampling method. Data were analyzed using multiple linear regression analysis, descriptive methods and inferential statistics. Hypothesis testing was done through the t test and F test. The descriptive analysis revealed that : 1) ROE earns an average of 9,9363% of total capital, 2) DAR shows that every Rp. 1 liability can be fulfilled with Rp. 34,5820 total assets, 3) DER shows that every Rp. 1 liability can be fulfilled with Rp. 73,4167 total equity. The results of the t test statistic showed that partially, the DAR variable had a negative and significant effect on ROE, then the DER variable had a positive and significant effect on ROE. The results of the F test statistic showed that simultaneously, all independent variables had a significant effect on ROE. The determination analysis revealed that the two independent variables were able to explain the variation in ROE of Cement Sub Sector companies of 59,6%.